2021
DOI: 10.3389/fneur.2020.627077
|View full text |Cite
|
Sign up to set email alerts
|

Optic Perineuritis and Its Association With Autoimmune Diseases

Abstract: Background: Optic perineuritis (OPN) is a special optic neuropathy that has a distinct etiology from neuromyelitis optica spectrum disorders (NMOSDs) or multiple sclerosis (MS)-related optic neuritis (ON). The mechanisms of how this inflammation developed and invaded the nerve sheath remain unknown. This study is aimed to analyze the etiology and different clinical characteristics of OPN in a Chinese patient population.Methods: Neuro-ophthalmological examination, orbit magnetic resonance imaging (MRI) and a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Thus, meningeal lesions affect the ONS. 12 Previous cases have indicated that the ONS and optic nerve are associated with carcinoma through paraneoplastic syndrome 13 and metastasis. 14,15 Metastasis of meningeal lesions also affects the ONS and optic nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, meningeal lesions affect the ONS. 12 Previous cases have indicated that the ONS and optic nerve are associated with carcinoma through paraneoplastic syndrome 13 and metastasis. 14,15 Metastasis of meningeal lesions also affects the ONS and optic nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Enhancement of the optic nerve sheath on axial and coronal post-contrast images suggested optic perineuritis. 12 …”
Section: Methodsmentioning
confidence: 99%
“…Recently, a case of anti-Asialo GM1 antibody-positive optic nerve and OPN in chronic inflammatory demyelinating polyneuropathy was reported [34]. In Graves’ disease in addition to prominent thickening and protrusion of extraocular muscles, orbital fat inflammation, and abnormal enhancement on the attachment point of the extraocular muscle was always associated with inflammation of the optic nerve sheath [12 ▪ ].…”
Section: Etiologymentioning
confidence: 99%
“…Central vision is usually spared. Visual field defects may include enlarged blind spots, arcuate and paracentral scotomas, peripheral island and altitudinal defects, and, rarely, central defects [4,8 ▪ ,12 ▪ ,15]. One case reported binasal hemianopia in bilateral OPN with presumed sarcoidosis, attributed to irreversible ischemic change in bilateral uncrossed optic nerve fibers [15].…”
Section: Clinical Featuresmentioning
confidence: 99%